MOBILITY AND RETENTION OF TRACE ELEMENTS IN HARDPAN-CEMENTED CASSITERITE TAILINGS, NORTH QUEENSLAND, AUSTRALIA - Lottermoser B.G.; Ashley P.M. (My University, 2006)
This study reports on the mobility and retention of trace elements in cassiterite tailings at the inactive Jumna mill, tropical north Queensland. Since the 1980s, the uncapped tailings have developed laterally discontinuous Fe-rich hardpans, which are located in the higher parts of gently sloping tailings masses and at the top (<50 cm) of the tailings piles. hardpan-cemented comprise thin layers (typically ~0.2-2 mm thick) hfo (hydrous ferric oxides) and sulfate efflorescences cementing grains. in comparison to tailings, contain significantly higher median as, ca, cd, co, cu, fe, in, mn, mo, s total, Th, U, Y and Zn values. Partial leaching studies of tailings and pond water analyses indicate that wetting and acidification of Fe-cemented tailings removes significant proportions of trace elements into pore and surface waters. Tin shows no mobility due to the presence of weathering-resistant cassiterite (SnO2) and, As and Pb display limited mobility possibly due to their coprecipitation with jarosite-type phases and HFO materials at the top of the tailings profile. By contrast, the trace elements Cd, Ce, Cu, La, Ni, Pb, U and Zn display the greatest mobility, possibly due to their incorporation in soluble sulfate efflorescences and sorption onto mineral and HFO surfaces. Hence, the Fe-rich hardpans do not protect the sulfidic tailings from further oxidation nor do they cause permanent sequestration of trace elements. © Springer-Verlag 2006.
Keywords: ACID MINE DRAINAGE; AUSTRALIA; CEMENTED LAYER; GEOCHEMISTRY; HARDPAN; MINERALOGY; SULFIDE OXIDATION; TAILINGS